Adherence to the EAT-Lancet reference diet is associated with a reduced risk of incident cancer and all-cause mortality in UK adults - Karavasiloglou, Nena; Thompson, Alysha S.; Pestoni, Giulia; Knuppel, Anika; Papier, Keren; Cassidy, Aedín; Kühn, Tilman; Rohrmann, Sabine (One earth, 2023)
Food systems have been identified as significant contributors to the global environmental emergency. However, there is no universally agreed-upon definition of what constitutes a planetary healthy, sustainable diet. In our study, we investigated the association between the EAT-Lancet reference diet, a diet within the planetary boundaries, and incident cancer, incident major cardiovascular events, and all-cause mortality. Higher adherence to the EAT-Lancet reference diet was associated with lower incident cancer risk (hazard ratio [HR]continuous: 0.99; 95% confidence interval [CI]: 0.98-0.99]) and lower all-cause mortality (HR continuous: 0.98; 95% CI: 0.98-0.99), while mostly null associations were detected for major cardiovascular event risk (HR continuous: 1.00; 95% CI: 0.98-1.01). Stratified analyses using potentially modifiable risk factors led to similar results. Our findings, in conjunction with the existing literature, support that adoption of the EAT-Lancet reference diet could have a benefit for the prevention of non-communicable diseases.
Online verfügbar: 21. November 2023, Artikelversion: 15. Dezember 2023
Gesehen am 10.05.2024